- Identification and evaluation the attractiveness of tourist places - A study in the geography of tourism - Al Shamri, Hamoud; Al-Shabaan, Ahmed Mohammed (Journal of Humanities & Social Sciences, 2018)
The aim of this study was to evaluate the places of natural and human tourism potential in Hail region and to evaluate the degree of variation in the attractiveness of tourist sites. The descriptive method was used، 1000 questionnaires were distributed and the study was applied to a random sample of 763 individuals in the study community. Know the degree of attractiveness of tourist sites (high، medium، low). In order to analyze the data of the study، some statistical tests were used such as (kay test)، mono- variance، frequencies and percentages، represented by tables and graphs. The geographical information system (GIS) tool was also used to determine tourist sites. Natural and human tourism، by determining the attractiveness of these sites، it was found that there were (11) high- attract tourist sites، 25 medium gravity sites، and 2 low- gravity sites، and that the area was a family tourist attraction. The study concluded with some recommendations.